A quality control study metal press and assembly - Barreto, Ronilon M.; Mandapat, Ronald Vincent E.; Reyes, Olaf Aaron C.; Taningco, Tristan Jan E. (College of Engineering, 1997)
Metal Press and Assembly, Inc. is a fabrication company that manufactures metal parts for multinational electronics companies, namely Sharp Phils., Matsushita Electric Co. and Mitsubishi Inc. The study is limited to production processes and quality assurance activities that MP&A produces for Sharp, namely the Speaker Grille, Brake Arm, Fan, Pulley, Side Speaker Assembly. The group conducted a series of plant visits, personnel interviews and review of historical data to document the production processes for the products, and the relevant quality activities. The group used various techniques to analyze the data gathered, namely the Failure Mode and Effects Analysis, the Ishikawa Diagram, the Pareto and Historigram charting, Quality Audit Questionnaire. The group analyzed the data gathered using a two-phase approach. First, the critical manufacturing process with the most fraction defective was identified, and the causes of this were noted. Second, the various quality activities were evaluated using a Quality Audit Questionnaire to identify flaws in the quality activities' procedures. The blanking process was the most critical process. Causes of its high lot rejection rate of the customer were identified as insufficient measures for die maintenance, gloves got caught in wire, misplacement of metal feeds, and irregular machine maintenance. In the quality activities, unsystematic sampling in the in-process inspection was noted as the critical causes of high rejection rates. The group drafted the following recommendations to attend to these critical causes of high customer rejection rates : regular maintenance check up for dies, restamping of expired dies, better gloves, additional guides, documentation of historical files of machine maintenance, and a new sampling plan using a lot size of 1000 unit, a sample number of 80 units and an acceptance number of 1 unit.